Computed tomographic features of the proximal petrous facial nerve canal in recurrent Bell's palsy. Issue 4 (9th June 2021) - Touska, Philip; Dudau, Cristina; Patel, Janki; Montvila, Antanas; Pucetaite, Milda; Obholzer, Rupert; Pai, Irumee; Connor, Steve
Abstract: Objectives: The primary objective was to determine whether the narrowest dimensions of the labyrinthine facial nerve (LFN) canal on the symptomatic side in patients with unilateral recurrent Bell's palsy (BP) differ from those on the contralateral side or in asymptomatic, age‐ and gender‐matched controls on computed tomography (CT). The secondary objectives were to assess the extent of bony covering at the geniculate ganglion and to record inter‐observer reliability of the CT measurements. Methods: The dimensions of the LFN canal at its narrowest point perpendicular to the long axis and the extent of bony covering at the geniculate ganglion were assessed by two radiologists. Statistical analysis was performed using the Wilcoxon signed‐rank and Mann‐Whitney U tests (LFN canal dimensions) and the Chi‐squared test (bony covering at the geniculate ganglion). Inter‐observer reliability was evaluated using Intra‐Class Correlation (ICC) and Cohen's kappa. Results: The study included 21 patients with unilateral recurrent BP and 21 asymptomatic controls. There was no significant difference in the narrowest dimensions of the ipsilateral LFN canal when compared to the contralateral side or controls ( P  = .43‐.94). Similarly, there was no significant difference in the extent of bony covering at the geniculate ganglion when compared to either group ( P  = .19‐.8). Good inter‐observer reliability was observed for LFN measurements (ICC = 0.75‐0.88) but not for the bony covering at the geniculate ganglion (Cohen's kappa = 0.53). Conclusion: The narrowest dimensions of the LFN canal and the extent of bony covering at the geniculate ganglion do not differ in unilateral recurrent BP, casting doubt over their etiological significance. Level of Evidence: Level IV. Abstract : Two observers evaluated the narrowest dimensions of the labyrinthine facial nerve canal and the extent of bony covering at the geniculate ganglion on computed tomography (CT), in 21 patients with unilateral recurrent Bell's Palsy and 21 matched asymptomatic controls. There was no significant difference in the dimensions of the ipsilateral (symptomatic) labyrinthine facial nerve canal or the geniculate ganglion bony covering in patients with unilateral recurrent Bell's Palsy, either when comparing to the contralateral side or to asymptomatic controls. This casts doubt over their aetiological significance of these CT findings in cases of recurrent BP.